Islamic Moderation and Counter-Radicalisation: Pedagogical Frameworks in Indonesian Pesantren - Syafiqurrahman; Syihabuddin Qalyubi; Khotimah Suryani (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2026)
This article develops a comprehensive integrative conceptual framework for religious moderation in pesantren education by systematically synthesising academic literature published between 2015 and 2025. Employing a systematic literature review combined with critical discourse analysis, this study analysed 43 peer-reviewed publications sourced from major Islamic education databases, identifying patterns in theoretical approaches, pedagogical strategies, and research gaps. Three dominant theoretical paradigms are identified: (1) the Traditionalist-Theological paradigm, which grounds moderation in the retrieval of classical Islamic scholarship; (2) the Neo-Modernist paradigm, which advocates progressive reinterpretation of Islamic sources; and (3) the Socio-Political paradigm, which critically examines moderation as a state-driven governance technology. Across these paradigms, four complementary pedagogical approaches are identified: classical text interpretation (kitab kuning), kiai leadership and moral exemplarity, hidden curriculum and organisational culture, and local wisdom integration (kearifan lokal). The findings reveal persistent conceptual tensions, contested definitions of moderation, methodological limitations in measuring attitudinal change, and inadequate engagement with digital-era challenges. This article proposes an integrative framework bridging classical Islamic concepts with transformative education theory and identifies five priority areas for future research. Findings carry direct implications for curriculum development, teacher professional development, policy formulation, and counter-radicalisation strategies across Muslim-majority societies globally.